The Domino Effect and the Supervision of the Banking System - PAROUSH, JACOB (Journal of Finance, 1988)
ABSTRACT The paper models the domino effect and defines a measurement for the necessity of banking supervision. The effect of several factors, such as the desired stability of the banking system, its size, the amount of negative externalities that are considered by banks, and supervisory costs, on the necessity of supervision are studied. For instance, it was found that, under certain circumstances, supervision becomes less essential if the number of banks increases. The paper has also emphasized that objective difficulties in the supervision of banks, by simply imposing restrictions on their activities, are intrinsic to the operation of the banks themselves. The paper provides some insight into the current debate as to the necessity or redundancy of supervision and regulation.